Meso‐Diketopyripentaphyrin and Diketopyrihexaphyrin as Macrocyclic Tripyrrinone Ligands for NiII Ions. Issue 23 (28th November 2019) - Mori, Daiki; Yoneda, Tomoki; Suzuki, Masaaki; Hoshino, Tyuji; Neya, Saburo
Abstract: We report expanded porphyrins with pyridine rings and two neighboring carbonyl groups, which allow Ni II ions to coordinate to the tripyrrinone‐type NNNO coordination structure with Ni−O bonds. The selectivity of tripyrrinone is superior to other pyrrolic or pyridinic cavities of expanded porphyrins. Introduction of α‐carbonyl pyridine next to the tripyrrolic conjugated structure is a powerful strategy for regioselective metalation of flexible expanded porphyrinoids. Abstract : Expanded porphyrins with a pyridine unit between two meso ‐carbonyl groups are reported. They coordinate to Ni II ions to produce a tripyrrinone‐type NNNO coordination structure. Coordination of the tripyrrinone units is highly regioselective in expanded circular pyriporphyrins with many coordination cavities in their structure.